Komunikasi Intrapersonal Dalam Komunikasi Islam - Rahmiana (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2019)
The purpose of writing Intrapersonal Communication in Islamic Communication is to find out the extent of the impact of intrapersonal communication itself on changes in a person's behavior and also his perspective on a problem. However, the problem is that intrapersonal communication cannot be known clearly and in plain view, so communication like this is difficult to see the process of ongoing communication so it will also be difficult to assess the impact it has caused. This writing will focus on the description of intrapersonal communication in Islamic communication and what is included in intrapersonal communication and its impact on the person's daily behavior. The question that then arises is what is meant by communication, intrapersonal communication and intrapersonal communication in Islamic communication, as well as what is included in intrapersonal communication. The opinions of experts discussing this matter are Blake and Harodlsen and Hafied Cangara. The results of this study are expected to provide positive added value for readers and can change the way to communicate towards a better direction.